QUALITY CONTROL OF FLOUR AND BAKERY PRODUCTS BY SCORE (American Journal of Interdisciplinary Research and Development, 2022)
The article provides a manual of standard generally accepted and methods for the study of bakery products with a logical structure that allows you to easily orient all the necessary methods for the study of bakery products.